Analisis Penggunaan Perala Tan Apron Movement Control (AMC) dalam Mendukung Keselamatan Penerbangan di Bandar Udara Internasional Juanda Surabaya - Arya Satya Putra Anugrah; Septiyani Putri Astutik (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
In the airport there is one important unit which is Apron Movement Control (AMC) as the person in charge of flight operations at the airport. Its performance is good greatly influences the success of a flight. Supporting equipment owned AMC units must be used and maintained as well as possible to do a good job also. Some negligence in not using mandatory equipment when in the field is also common occurred especially at Juanda Airport in Surabaya. This research uses a type of research with a qualitative descriptive method. For To get answers from the research, the researcher creates a research design. Qualitative research is research used to investigate, discover, describe, and explain the quality of influence that cannot be explained, measured or described through a quantitative approach. The research results show that all AMC unit officers understand and are capable operate equipment well, tasks can be done well with the equipment it is complete and suitable for use. Officers can guarantee successful safety although it cannot be denied that the success of this flight depends on readiness and discipline of officers in carrying out themcontrolling etc.